2019
DOI: 10.1038/s41428-019-0242-z
|View full text |Cite
|
Sign up to set email alerts
|

Periodic introduction of aromatic units in polypeptides via chemoenzymatic polymerization to yield specific secondary structures with high thermal stability

Abstract: Polypeptides containing periodic aromatic residues in their main chains were synthesized via papain-catalyzed chemoenzymatic polymerization of tripeptide ester monomers under moderate conditions in aqueous buffers. As the monomer, 4-aminobenzoic acid (Abz) was modified with Gly or Ala at the N-and C-termini to mitigate the poor substrate specificity of papain to unnatural amino acids. The tripeptide esters, namely, GlyAbzGly and AlaAbzAla ethyl esters, can be recognized and polymerized by papain, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…To polymerize N ε -Boc-protected l -lysine methyl ester, we used chemoenzymatic polymerization according to the previous literature. , A solution of N ε -Boc-protected l -lysine methyl ester hydrochloride (5 g, 16.8 mmol) in phosphate buffer (8.4 mL, 1.0 M, pH = 8.0) was placed in a glass tube equipped with a stirring bar. To this was added a solution of papain (0.84 g) in phosphate buffer (5.6 mL) in one portion.…”
Section: Methodsmentioning
confidence: 99%
“…To polymerize N ε -Boc-protected l -lysine methyl ester, we used chemoenzymatic polymerization according to the previous literature. , A solution of N ε -Boc-protected l -lysine methyl ester hydrochloride (5 g, 16.8 mmol) in phosphate buffer (8.4 mL, 1.0 M, pH = 8.0) was placed in a glass tube equipped with a stirring bar. To this was added a solution of papain (0.84 g) in phosphate buffer (5.6 mL) in one portion.…”
Section: Methodsmentioning
confidence: 99%
“…Supramolecular nanostructures, which consist of selfassembling peptide derivatives, have attracted rapidly increasing attention for the fabrication of various biofunctional materials [1][2][3][4][5][6][7][8][9]. Recent seminal works have revealed that short peptides bearing an aromatic group at their N-termini have a robust potential to self-assemble into supramolecular nanostructures under aqueous conditions with subsequent hydrogel formation, facilitating active exploration [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, unnatural amino acid monomers are tightly excluded during the enzymatic reaction� Our initial attempt to polymerize unnatural amino acid esters in the presence of various proteases was not satisfactory: the amount of unnatural amino acids that can be incorporated into polypeptide sequences is quite limited, 12 which motivated us to design unnatural amino acid-containing oligopeptide ester monomers� Sandwiching the unnatural amino acids amid natural amino acids allows proteases to recognize such species in the substrate pocket, leading to successful polymerization of these oligopeptide monomers (Figure 4). [13][14][15] A typical unnatural amino acid, 2-aminoisobutyric acid (Aib), is an α,α-disubstituted amino acid with bulky side groups. Introduction of Aib residues in polypeptides is known to strongly induce a helical conformation due to the bulky structure� We prepared a tripeptide ethyl ester with an alanine-Aib-alanine (AlaAibAla) sequence for the monomer for chemoenzymatic polym-erization� 15 Neither nor a Aib-containing dipeptide monomer was found to be able to polymerize in the presence of papain because the Aib unit has a poor affinity for papain.…”
Section: Unnatural Polypeptidesmentioning
confidence: 99%